Survival of patients with cirrhosis and acute peptic ulcer bleeding compared with variceal bleeding using current first‐line therapies. Issue 4 (18th February 2018) - Ardevol, Alba; Ibañez‐Sanz, Gemma; Profitos, Joaquim; Aracil, Carles; Castellvi, Josep M.; Alvarado, Edilmar; Cachero, Alba; Horta, Diana; Miñana, Josep; Gomez‐Pastrana, Bárbara; Pavel, Oana; Dueñas, Eva; et al.
Abstract : The presence of cirrhosis increases the mortality of patients with peptic ulcer bleeding (PUB). Both acute variceal bleeding (AVB) and PUB are associated with substantial mortality in cirrhosis. This multicenter cohort study was performed to assess whether the mortality of patients with cirrhosis with PUB is different from that of those with AVB. Patients with cirrhosis and acute gastrointestinal bleeding were consecutively included and treated with somatostatin and proton pump inhibitor infusion from admission and with antibiotic prophylaxis. Emergency endoscopy with endoscopic therapy was performed within the first 6 hours. 646 patients with AVB and 144 with PUB were included. There were baseline differences between groups, such as use of gastroerosive drugs or β‐blockers. Child‐Pugh and Model for End‐Stage Liver Disease MELD scores were similar. Further bleeding was more frequent in the AVB group than those in the PUB group (18% vs. 10%; odds ratio [OR] = 0.50; 95% confidence interval [CI] = 0.29‐0.88). However, mortality risk at 45 days was similar in both groups (19% in the AVB group vs. 17% in the PUB group; OR = 0.85; 95% CI = 0.55‐1.33; P = 0.48). Different parameters, such as Child‐Pugh score, acute kidney injury, acute on chronic liver failure, or presence of shock or bacterial infection, but not the cause of bleeding, were related to the risk of death. Only 2% of the PUB group versus 3% of the AVB group died with uncontrolled bleeding ( P = 0.39), whereas the majority of patients in either group died from liver failure or attributed to other comorbidities. Conclusion: Using current first‐line therapy, patients with cirrhosis and acute peptic ulcer bleeding have a similar survival than those with variceal bleeding. The risk of further bleeding is higher in patients with variceal hemorrhage. However, few patients in both groups died from uncontrolled bleeding, rather the cause of death was usually related to liver failure or comorbidities. (Hepatology 2018;67:1458‐1471).